Mechanical properties and microstructures of bio-inert layers of chrome oxide coatings deposited by the APS process - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Plasma spray Cr2O3 ceramic layers are used as a separate coating or as a supplement to bio-reactive organic composite ceramics Ca10(PO4)6(OH)2-Al2O3-ZrO2-Cr2O3 and other bio-inert ceramics in composites of the types Al2O3–ZrO2–SrO–Cr2O3–Y2O3, ZrO2-TiO2-Cr2O3 and TiO2-Cr2O3 to increase the mechanical properties and resistance components of artificial joints on sliding abrasion and corrosion. This paper analyzes the influence of the plasma gun distance from the substrate on the mechanical properties and the microstructure of Cr2O3 layers deposited with the current of 40kW. The aim was to deposit layers with optimal characteristics that will enable the effective implementation of Cr2O3 layers on substrates of steel implants exposed to dry friction without lubrication and to corrosion of living tissues. The mechanical properties were tested by examining microhardness layers using the HV0.3 method and the strength was tested by tensile testing. The surface of powder particles was examined by SEM. The microstructures of layers were analyzed with the use of an optical microscope (OM) and a scanning electron microscope (SEM). The test results confirmed a possibility of effective application of bio-inert layers of Cr2O3 with other ceramics intended for the production of functional implants.